2007
DOI: 10.1074/jbc.m607849200
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Channel A1 Is Directly Gated by Calcium Ions

Abstract: Members of the superfamily of transient receptor potential (TRP) channels are proposed to play important roles in sensory physiology. As an excitatory ion channel TRPA1 is robustly activated by pungent irritants in mustard and garlic and is suggested to mediate the inflammatory actions of environmental irritants and proalgesic agents. Here, we demonstrate that, in addition to pungent natural compounds, Ca 2؉ directly gates heterologously expressed TRPA1 in whole-cell and excised-patch recordings with an appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
265
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(289 citation statements)
references
References 29 publications
20
265
3
1
Order By: Relevance
“…Taken together, these data demonstrate that thermal and chemical sensitivities are specified by a portable N-terminal ARrich domains of the channel. Mammalian TRPA1 channels can also be activated by intracellular calcium (8,(22)(23)(24), and we therefore asked whether heat-evoked responses of the human-rattlesnake chimera 3 were still observed when oocytes were loaded with the calcium chelator 1,2-bis(o aminophenoxy) ethane-N,N,N′,N′-tetraacetic acid (BAPTA) and perfused with calcium-free medium. Chelation of cytoplasmic calcium did not eliminate heat-evoked currents (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, these data demonstrate that thermal and chemical sensitivities are specified by a portable N-terminal ARrich domains of the channel. Mammalian TRPA1 channels can also be activated by intracellular calcium (8,(22)(23)(24), and we therefore asked whether heat-evoked responses of the human-rattlesnake chimera 3 were still observed when oocytes were loaded with the calcium chelator 1,2-bis(o aminophenoxy) ethane-N,N,N′,N′-tetraacetic acid (BAPTA) and perfused with calcium-free medium. Chelation of cytoplasmic calcium did not eliminate heat-evoked currents (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that calcium potentiates TRPA1 activity, followed by a process of calcium-dependent desensitization or inactivation (8,(22)(23)(24). Despite the potential relevance of these phenomena to nociceptor excitability and inflammatory pain (7, 16), mechanisms underlying calcium-dependent TRPA1 modulation remain controversial, with some groups favoring direct binding of calcium to an EF hand-like motif within the N-terminal domain (22,23) and others advocating a calmodulin-or EF hand-independent process of unknown nature (24). Interestingly, we found that rattlesnake TRPA1 channels show calcium-dependent potentiation (52 ± 6%, n = 3; Fig.…”
Section: Ar-containing Region Of the N Terminus Modulates Chemicalmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that TRPA1 is often desensitized in the presence of extracellular Ca 2+ [10,30]. It has even been reported that calcium ions alone can directly gate heterologously expressed TRPA1 [31,32]. Therefore, many researchers choose to use a calcium-free solution in the patch clamp experiment to avoid desensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many researchers choose to use a calcium-free solution in the patch clamp experiment to avoid desensitization. However, some reported TRPA1 agonists such as icilin, which uses a different activation mechanism to other TRPA1 agonists, display a requirement for calcium ions to elicit an agonist response [31,33]. Calcium ions were shown to potentiate the agonist-mediated activation of TRPA1 without changing the property of the agonists.…”
Section: Discussionmentioning
confidence: 99%